Report on industrial attachment with Sun Microsystems, Singapore - Koh, Jimmy Kok Heng. (2008)
The report consists of two phase of training learnt: improving Solaris/Unix proficiency as well as getting an in-depth knowledge of the workings of Sunes products; taking Serengeti mid-ranger server tasks/calls, assuming the role of a PTS engineer.